Planning in turbulent times: exploring planners' agency in Jerusalem - Rokem, J. (2016)
This article explores the role of planning in the deeply divided and politically polarized context of Jerusalem. The overall argument developed throughout the article is that the relation between planning and politics is a non-hierarchical set of interactions, negotiated within specific historical, geographical, legal and cultural contexts—in other words, orders don't come down from the politicians to be slavishly followed by planners. In this respect our findings, based on in-depth interviews with Israeli planners, suggest that the case of Jerusalem represents a particularly dramatic illustration of the fact that the function of planning expertise can only be understood in relation to the surrounding socio-political environment. Furthermore, contrary to conventional wisdom, planners in Jerusalem are not destined to either complicity or irrelevance in the face of political imperatives; planners' agency, however, does not simply reflect their mastery of specific professional knowledge and tools, but also their ability to act strategically in relation to the context in which they operate.